2018
DOI: 10.1029/2017jc013624
|View full text |Cite
|
Sign up to set email alerts
|

Water Column Stability and the Role of Velocity Shear on a Seasonally Stratified Shelf, Mississippi Bight, Northern Gulf of Mexico

Abstract: Water column stability is a critical component of coastal systems, regulating the vertical exchange of momentum, mass, and biogeochemical constituents. Observations of water column velocity and hydrographic conditions during the summer of 2010 were used to investigate aspects of the region of freshwater influence in the Mississippi Bight. Conductivity‐temperature‐depth surveys south of Mobile Bay indicated strong stratification (peak buoyancy frequencies ~0.09–0.3 s−1) across the inner and midshelf. Despite th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
5
9
0
Order By: Relevance
“…In addition to a convergence mechanism, the model output indicates that there was consistent vertical shear at the time and location of the thin layer. The model shear levels are consistent with previous regional observations (Dzwonkowski et al 2018a). Assuming the physical convergence in the model output is a key mechanism in producing the initial patch, the model shear is representative, and a reasonable turbulent diffusion coefficient can be determined.…”
Section: Model Mechanism Of Thin Layer Formationsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition to a convergence mechanism, the model output indicates that there was consistent vertical shear at the time and location of the thin layer. The model shear levels are consistent with previous regional observations (Dzwonkowski et al 2018a). Assuming the physical convergence in the model output is a key mechanism in producing the initial patch, the model shear is representative, and a reasonable turbulent diffusion coefficient can be determined.…”
Section: Model Mechanism Of Thin Layer Formationsupporting
confidence: 80%
“…Although the nGOM appears to have favorable conditions for thin layer formation (Dzwonkowski et al 2018a), there are surprisingly few studies in this region and other coastal riverdominated ecosystems (but see Churnside and Donaghay 2009). The nGOM is known for high biological and overall fisheries production (Grimes 2001), which is generally attributed to the extensive riverine nutrient input fueling higher primary productivity relative to other marginal seas (> 300 g C m −2 yr −1 ; Heilman and Rabalais 2008;Lohrenz et al 2014).…”
Section: Thin Layers In the Ngommentioning
confidence: 99%
“…3a) as well as the lack of tropical storm activity during the summer 2016, the ship transects are likely representative of shelf hydrographic conditions in the Mississippi Bight. The observed stratification levels in 2016 are consistent with previous regional work of water column stability that have measured buoyancy frequencies on the order of 0.07-0.20 s -1 (Belabbassi, 2006;Dzwonkowski et al, 2018), similar to conditions observed on the Texas-Louisiana Shelf, i.e., buoyancy frequencies~0.07-0.28 s -1 (Wiseman et al, 1997;Belabbassi, 2006;Bianchi et al, 2010). However, the sources of the shelf stratification in the Mississippi Bight appear less straightforward.…”
Section: Physical Characterization Of Mississippi Bightsupporting
confidence: 88%
“…2e and 3a). These features in the temperature structure are characteristics of downwelling events 24 , which highlights the established importance of three-dimensional processes associated with hurricane responses in the coastal ocean 7,8 . This model limitation imparts a cold bias in temperature outputs at the start of the post TS Gordon period with the depth-average temperatures in the different A cases being between~1 and 3°C cooler than the observations (~September 7, Fig.…”
Section: Resultsmentioning
confidence: 87%